Optimalisasi Media Online dalam Pengembangan Wirausaha Ibu PKK Tunjungsekar - Juliati; Lestari, Ida Puji (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
PKK as social organization aims to improve family welfare. This can be done by empowering women. One of the efforts to empower women is to increase knowledge and skills that will enable them to be independent and contribute to improving family welfare. Entrepreneurship training is one of the appropriate training given to PKK members. From th team’s observation, PKK in RT 03 RW 4 Tunjungsekar Village still needs more positive activities for its members. The lack of training activities given to the members has encouraged the team to carry out the community service for PKK RT 03 members. Entrepeneurship training was chosen because it is appropriate skill to be given to them because many of them are housewives and especially to those who live in the small alleys. Those who live along the kampong street, some have tried to open business such as selling food and drinks, and groceries. This entrepreneurship training is expected will increase their knowledge, motivation and skills to open a business to improve their family welfare. After the workshops were conducted especially the one dealt with the use of social media and internet in business, the participants looked satisfied and expected that the team would carry out such workshop in the following years. Keywords: workshop; entrepreneurship; PKK